2019
DOI: 10.4236/ojanes.2019.93005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Formula for Calculation of the Optimal Insertion Depth for Cuffed Endotracheal Tubes in Pediatric Major Surgery

Abstract: Background: Accurate determination of the optimal insertion depth of a pediatric endotracheal tube (ETT) is quite important. The aim of this study was to create an easily available formula that can be used to determine the optimal insertion depth for a cuffed ETT even without depth marking with clear definitions of the upper and lower limits for the tip of ETT in the trachea in clinical practice. Methods: Eighty children under 12 years of age were enrolled. The depth marking of the cuffed ETT was placed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, they used cuffed ETTs and had different numeric variables in the formulae. 3 The incidence of distal intubation was found to be 74% in our study group with an accurate placement seen only in 13 patients. The subgroup analysis in the present study showed 30% appropriate depth in age group of 1-2 years, 42.8% in 2-3 years, and 6.25% in 3-4 years subgroup.…”
Section: Ta B L E 1 Demographic Characteristics and Ett Depth Values Using Different Formulae In Age Subgroupsmentioning
confidence: 49%
See 1 more Smart Citation
“…However, they used cuffed ETTs and had different numeric variables in the formulae. 3 The incidence of distal intubation was found to be 74% in our study group with an accurate placement seen only in 13 patients. The subgroup analysis in the present study showed 30% appropriate depth in age group of 1-2 years, 42.8% in 2-3 years, and 6.25% in 3-4 years subgroup.…”
Section: Ta B L E 1 Demographic Characteristics and Ett Depth Values Using Different Formulae In Age Subgroupsmentioning
confidence: 49%
“…1,2 Various formulae have been studied for determining the accurate ETT depth in children. [3][4][5][6] These formulas are either complex 4 or have suboptimal accuracy. 5,6 Age-, 7 weight-, 8 and height-based 9 formulae have been frequently used to predict the optimum ETT depth in children.…”
Section: Introductionmentioning
confidence: 99%